Transitioning children with disabilities : from early childhood through adulthood - Ellis, Antonio L. (Studies in inclusive education (Sense Publishers), 2017)
This book is an authoritative volume of scholarship through qualitative and quantitative methodologies on postsecondary transition services for a diverse readership. The editor's intended audience is composed of students with disabilities, school administrators, special education coordinators, colleges and university faculty, staff, and administrators, among other scholars, practitioners, and advocates. Readers of this volume will be educated on the postsecondary transition process, and the lifelong commitment of educators who guides students with disabilities through their rigorous, yet rewarding journey. This book also can be used by student personnel administrators, employers, student retention coordinators, and workforce development professionals to improve the implementation of postsecondary transition services. The importance of comprehensive transition planning for students with disabilities is the impetus for bringing this collaborative effort to print. Topics in this volume highlight areas that have critical implications for children and adolescents' preparation for adulthood. Contributors' presents potent research regarding various topics addressing P-16 students' needs, and have been active practitioners in both areas - transition services and disabilities as defined under the Individuals with Disabilities Education Act (IDEA) of 2004. Ultimately, this book is a collection of interrelated chapters that offer rich content and insights into current trends for individuals with disabilities who are moving through various stages of their lives.